Variation of cervical sagittal alignment parameters according to age and pelvic incidence in degenerative spinal deformity patients - Lamas, Vincent; Chapon, Renan; Prost, Solène; Blondel, Benjamin; Fuentes, Stéphane; Sauleau, Erik André; Charles, Yann Philippe (European spine journal, 2023)
Introduction In asymptomatic subjects, variations of cervical sagittal alignment parameters according to age and spinopelvic organization have been reported. A large range of compensation phenomena has been observed in degenerative spinal deformity in order to maintain horizontal gaze, but it remains unclear how age and spinopelvic morphology could additionally influence cervical alignment. The aim of this observational retrospective study was to describe the distribution of cervical sagittal alignment parameters according to age and pelvic incidence in subjects with and without degenerative spinal deformity in order to precisely evaluate cervical compensation phenomena in adult spinal deformity (ASD). Material and methods Radiographs of 478 subjects (327 females and 151 males) were distributed into 235 asymptomatic and 243 deformed subjects. Occipito-cervical parameters were McGregor-C1, McGregor-C2, C1–C2 and occipito-C2 angles. The cervicothoracic inflection point (CTIP) was determined. Caudal cervical sagittal alignment parameters were: C2–C7 lordosis, C2-apex (superior arch), apex-CTIP (inferior arch), occipito-C3 and occipito-C4 angles, C7-slope and T1-slope. The distribution of parameters was analyzed using a Bayesian inference (significant when Pr > 0.975 or Pr < 0.025). Comparisons between asymptomatic and deformed subjects were done after matching on age (40–60 years; > 60 years) and on PI (< 45°; 45–60°; > 60°). Results Among occipito-cervical parameters, there was no significant change in McGregor-C1 angle. However, McGregor-C2 angle was significantly higher in the ASD group (Pr = 0.0029), with influence of age (Pr = 0.023), but PI influence. C1–C2 lordosis was significantly higher in the ASD group compared to the asymptomatic group (Pr < 0.0007), without influence of age or PI noticed. C2–C7 lordosis was also higher in the ASD group (Pr < 0.025) with a role of age and PI (Pr < 0.025). Cervical lordosis in the superior arch was significantly higher in the ASD group (Pr > 0.999), without influence of age or PI. In the inferior arch, the lordosis angle was not modified according to the group, but there was an influence of age (Pr < 0.0007). C7-slope and T1-slope were higher according the age group (Pr < 0.0012), without influence of the group or PI. Conclusion This observational study highlights cervical sagittal alignment adaptations in degenerative spinal deformity, matched on age and pelvic incidence. The inferior cervical spine seemed to be modified with a higher lordosis, increasing with age responding to the age-related thoracic kyphosis increase. In addition to that, the superior cervical spine hyperextends more in adult degenerative deformity to maintain horizontal gaze. Level of evidence III.